INCREASING USE OF LAND CALCULATOR APPLICATIONS FOR HATIVE VILLAGE COMMUNITIES IN AMBON CITY - Latupapua, Yosevita Th; P. E. Papilaya, Patrich (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The millennial era has an impact that is digitally laden with the development of technology and information, so it needs to be utilized in improving self-ability and community empowerment. One of the efforts is to use an android application, Land Calculator to support community needs related to determining the boundaries of community-owned areas. Most people do not understand the use of this application. The purpose of the service in Hative village is to improve the ability and skills of the community in utilizing the Land Calculator application to obtain certainty about the boundaries of community-owned areas. The target subjects are heads of families who are domiciled in Hative village. The method used is direct learning through lectures and the practice of using the Land Calculator application in community-owned areas. The lectures were carried out with the intention that the public had initial knowledge about the Land Calculator application. After that, it was continued with mentoring during practice at community locations. The process of operating the Land Calculator application goes well. The results achieved show that there is a change in the level of understanding and enthusiasm among PKM participants. This is realized through the ability to independently use the Land Calculator application without having to be accompanied by a resource person.